Determination of Surface Finish Quality of Metals By Means of Optical Methods - Ariono Abdulkadir; Richard C. Birkebak (Institute for Research and Community Services (LPPM) ITB, 1974)
Ringkasan. Determination of surface - finish quality is done by measurements of its rms. Values of surface roughness and slopes. Mechanical measurements of these properties are done by using a profilometer. This method, however, is limited to surface having asperities larger then the size of the profilometer's tip and is of destructive type of testing. Alternate techniques using optical method based on the theories of Davies and Beckmann are presented. The instrumentation used was a double - beam, modified Perkin-Elmer 621 Spectrophotometer. Results using several randomly roughened metallic surface show good agreement with the existing theory and experimental results.Abstract. Pengukuran kekasaran permukaan-permukaan logam biasanya dilakukan dengan menentukan harga rms. dari seluruh distribusi jarak dari lembah kepuncak beserta orientasi dari setiap faset yang membentuk kekasaran permukannya. Pengukuran kebesaran-kebesaran ini secara mekanis dilakukan dengan mempergunakan profilometer. Akan tetapi, metoda ini terbatas untuk permukaan-permukaan yang ukuran ujung jarum profilometer yang dipakai; lagipula metoda ini termasuk dalam jenis yang disebut